Sexual dysfunction following spinal cord injury: the experiences of Malaysian women - Othman, A.S.; Julia, P.E. (2011)
The aim of the study is to assess the changes in sexual life and sexual function in women after spinal cord injury using the validated Malay Version of Female Sexual Function Index. Thirty-three women with spinal cord injury from the Spinal Rehabilitation Unit of a tertiary hospital in Malaysia participated in this study. A comparison was made between this group of women and a control group comprising 34 women matched for age and marital status. The findings showed that 40 of the women continued to have sexual activity after injury. Frequency of sexual activity and desire was lower among women with spinal cord injury, but the ability to achieve arousal, lubrication, orgasm and overall sexual satisfaction did not differ from those of the control group. These findings imply that it is possible for women with spinal cord injury to have an active, satisfying sexual life in spite of changes in sexuality caused by the injury.